Earthquake loss estimation for the Kathmandu Valley - Chaulagain, Hemchandra
Kathmandu Valley is geologically located on lacustrine sediment basin, characterized by a long history of destructive earthquakes. The past events resulted in large structural damage, loss of human life’s and property, and interrupted the social development. In recent years, the earthquake risk in this area has significantly increased due to uncontrolled development, poor construction practices with no earthquake safety provisions, and lack of awareness amongst the general public and government authorities. In this context, this study explores the realistic situation of earthquake losses due to future earthquakes in Kathmandu Valley. To this end, three municipalities: (a) Kathmandu Metropolitan City, (b) Lalitpur Sub-Metropolitan City and (c) Bhaktapur Municipality are selected for a case study. The earthquake loss estimation in the selected municipalities is performed through the combination of seismic hazard, structural vulnerability, and exposure data. Regarding the seismic input, various earthquakes scenario considering four seismic sources in Nepal are adopted. For what concerns the exposure, existing literature describing the construction typologies and data from the recent national census survey of 2011 are employed to estimate ward level distribution of buildings. The economic losses due to the earthquake scenarios are determined using fragility functions. Finally, the ward level distribution of building damage and the corresponding economic losses for each earthquake scenario is obtained using the OpenQuake-engine. The distribution of building damage within the Kathmandu Valley is currently being employed in the development of a shelter model for the region, involving various local authorities and decision makers.